Une autre façon d'être Grec : interactions et productions des Grecs en milieu colonial : Actes du colloque international organisé à Amiens (Université de Picardie Jules Verne/TRAME) et Paris (ANHIMA), 18-19 novembre 2016 = Another way of being Greek : interactions and cultural innovations of the Greeks in a colonial milieu - Costanzi, Michela; Dana, Madalina (Colloquia Antiqua (Series) ;, 2020)
"Research concerning the spread of Greeks in the Mediterranean has been characterised for the last 30 years by a persistent interest in the phenomena of hybridisation and cultural interaction. While paying tribute to the remarkable progresses in our knowledge of the 'colonial worlds', this volume offers a different approach of the exchanges that distinguished these societies. Our interest further embraces the activities and innovations of the Greeks in the colonial milieu, be it by transforming their cultural heritage, by exploiting the resources they found where they settled, or by adapting their practices under the influence of other Greeks. By focusing on these exchanges, the authors question the place of local connections in the construction of regional cultures, and their original features."--